Health policies and consolidated purchases of medicines (Teorías, Enfoques y Aplicaciones en las Ciencias Sociales, 2017)
The objective of this study is to characterize the behavior of consolidated purchases of medicines (CC), as a strategy of the most important public health policies of recent years to achieve cost containment since 2013. In addition, it is proposed to know if it has been achieved efficiency in spending that guarantees coverage of the needs of the population. To do this, it seeks to measure the efficiency of public expenditure (Ψ) in medicines by defining three goals: 1). "CC coverage index" (Θ). 2). "Expenditure Efficiency Index in CC per capita" (Λ). 3). "Composite Index of Price Dispersion" (ξ). This results in the Global Efficiency Index of the CC (Ψ); it will be done only with beneficiaries of the IMSS and the ISSSTE due to their better availability and information. The study carries out an evaluation of the consolidated purchases of medicines for the years 2013 to 2016, which are proposed as a public health policy aimed at containing expenditure and thereby achieving greater budgetary efficiency. It shows that there is a set of deficiencies that suggests the redesign and programming of the process in each of its stages. It is necessary that the authorities consider new criteria for the definition of drug codes that must participate and thus avoid an increasing number of empty codes, purchases outside of consolidated and non-compliance due to omissions of purchasing institutions as well as suppliers.
Keywords: public spending; consolidated purchases; global efficiency